Isolasi dan aktivitas antibakteri jamur endofit pada mangrove Sonneratia alba dari Tanjung Carat Kabupaten Banyuasin Sumatera Selatan - Anna Heirina; Rozirwan Rozirwan; Muhammad Hendri (Jurnal Penelitian Sains, 2020)
S. alba is a mangrove that is commonly found on the east coast of Banyuasin. Endophytic fungus can produce a functional compound e.g antibacterial. The purpose of this study is to determine the type, the increase in diameter of colonies and the antibacterial potential in endophytic fungus of S. alba. The research method used were by the isolation of endophytic fungus from leaf, stem and root, the identification of endophytic fungus, the measurement of colony diameter in endophytic fungus and antibacterial activity test using paper disc method. The results of this study found the two genera of endophytic fungus with four species of Aspergillus sp1., Aspergillus sp2., Paecilomyces sp1., and Paecilomyces sp2. The increase in diameter for each colony of endophytic fungus shows the difference every day. Aspergillus sp1. The exponential phase has been visible on the third day with an average diameter increase of 33.70 mm / day. The exponential phase of Aspergillus sp2 was visible on the third day with an diameter increase of 37.74 mm/day. In the endothelium fungi Paecilomyces sp1, the exponential phase was visible on the third day to the seventh day with diameter increase of 13.57 mm/day to 38.07 mm/day. Exponential phase of Paecilomyces sp2. was visible on the third day to the sixth day with diameter increase of 25.25 mm/day to 75.21 mm/day. These four types of endophytic fungus are resistant to bacteria E. coli and S. aureus. Aspergillus sp2. endophytic fungus has the highest inhibitor potency of 14.49 mm in E. coli bacteria. The endophytic fungus Paecilomyces sp2. inhibits bacterial growth of S. aureus with the highest inhibitory potency of 11.61 mm.